(untitled) (Revista Apotheke, 2020)
This paper presents our reflections and perceptions about the identity and formative processes of the Visual Arts teacher through photo-essays. It is inserted in the context of a research project which opted for Arts-Based Educational Research (ABER) as methodological reference (HERNÁNDEZ, MARTINS, DIAS) focusing on the contributions of photography as a research strategy and qualitative instrument (VIADEL, ROLDAN). It is expected to contribute to new reflections with the discussions on the more adequate methodology for contemporary issues which arise in the areas of art and education. They are not and not intend to be conclusive, but that they intend to expand the dialogue, more specifically, for the Visual Arts teacher education, under multiple perspectives, and with the collaboration between students and teachers, researchers and participants in the development of this research.